Estudio de la aplicación de la Inteligencia Artificial en la Administración de Justicia - Loaiza Orellana, Cinthya Carolina (2024)
The present research, titled "Study of the Application of Artificial Intelligence in the Administration of Justice," is aimed to analyze artificial intelligence in the administration of justice, regarding its use as a tool for the decongestion, streamlining, improvement, and strengthening of the justice system. Because of the advancement of artificial intelligence, new paradigms of analysis emerge for our benefit, making the work of justice operators faster and more efficient. The sudden advancement of artificial intelligence plays a leading role in a social transformation, and its development has generated widespread interest in its application in the field of law. Automation in certain justice administration processes is already a reality in Latin America which should be welcomed as it has the potential to solve conflicts swiftly and effectively. Artificial intelligence (AI) has the capacity to handle a wide range of information, serving objectively as an assistant to the judge. Therefore, it becomes crucial for the state to promote the application of artificial intelligence as an auxiliary tool for justice operators, aiming to strengthen the ecuadorian judicial system and progress towards the innovation and modernization of the legal field. This research encompasses pivotal aspects concerning artificial intelligence and its potential as a tool for justice operators, presenting an undeniable opportunity to enhance efficiency while respecting fundamental rights and principles determined in the Constitution of the Republic of Ecuador. In this research work, a variety of materials and methods were employed to carry out a solid investigation and achieve the established objectives. Surveys and interviews were conducted with professionals and experts in the field of laws, who provided valuable information for the analysis of the proposed topic.